Assessment worlds colliding? Negotiating between discourses of assessment on an online open course. (3rd May 2016) - Hills, Laura; Hughes, Jonathan
Abstract: Using the badged open course, Taking your first steps into Higher Education, this case study examines how assessment on online open courses draws on concepts of assessment used within formal and informal learning. Our experience was that assessment used within open courses, such as massive open online courses, is primarily determined by the requirements of quality assurance processes to award a digital badge or statement of participation as well as what is technologically possible. However, this disregards much recent work in universities that use assessment in support of learning. We suggest that designers of online open courses should pay greater attention to the relationship of assessment and learning to improve participant course completion.